An examination of UV radiation tolerance and photoenzymatic repair capabilities across temperature in the freshwater cladocerans Scapholeberis mucronata, Diaphanosoma birgei, and Moina spp. Issue 1 (1st January 2017) - Seitz, Harrison J.; Morgan, Micah L.; Kyllo, Thomas R.; Cooke, Sandra L.
ABSTRACT: Ultraviolet (UV) radiation has multiple consequences to freshwater organisms. Some zooplanktons use photoenzymatic repair (PER), which is a process that utilizes ultraviolet-A and visible light (photorepair radiation, PRR) to repair ultraviolet-B-induced DNA damage. Some zooplanktons also repair damage via nucleotide excision repair (NER), which is a radiation-independent enzymatic process. Our objective was to determine the effects of UV radiation, including the use of PER and NER on the cladocerans Diaphanosoma birgei, Scapholeberis mucronata, and Moina spp. Based on studies with Daphnia, we hypothesized that the use of PER and NER varies with temperature and across species. The three taxa were exposed to UV-B radiation followed by photorepair radiation (+PRR) or no photorepair radiation (−PRR). The occurrences of PER and NER were determined indirectly by monitoring the survival and reproduction after exposure. Experiments were performed at 10, 15, 20, 25, and 30 °C. S. mucronata and Moina spp. use PER effectively at all temperatures, whereas D. birgei uses PER less effectively and only at warmer temperatures. S. mucronata and Moina spp. use NER more effectively at colder temperatures, while D. birgei uses little to no NER. These findings have implications on how these organisms may adapt to changing UV and thermal conditions.